Orthopaedic and Trauma Services during COVID 19 at Karnali Academy of Health Sciences: an Early Experience - Rawal, Mangal; Kathayet, Tufan Singh; Mahaseth, Nirajan; Rokaya, Poojan Kumar; Samal, Anup Mangal; Devkota, Harihar; Bhattarai, Ramesh; Mahat, Smritee (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: World Health Organization (WHO) declared first pandemic caused by group of corona virus family, severe acute respiratory syndrome corona virus 2(SARS- CoV-2) on late 20201.One of the major challenges during the evolving COVID-19 pandemic was to deliver continuity of care to outpatients in the trauma and orthopaedic department. So, analysis of orthopaedic and trauma service during corona may provide overview of specialist care and its challenges during corona pandemic. Methods: All patients coming to Karnali Academy of Health Sciences from 14 March 2020 to 16 Sept 2020 were included and analyzed in terms of highest number of OPD, inpatient and OT cases. Clinical profiles, causes of admission, type of procedures were analyzed. Data analysis was done using excel and SPSS version 17. Results: Result were analysed on the basis of patients coming to OPD, Ward and Operation theater during 14 March 2020 to 16 Sept 2020.In OPD, out of 3035 cases, 27% was fracture .Majority of cases coming to OPD were male (57%).Total admission in orthopedic ward during this period was 249.Out of which majority were male (72%) with fracture being most common cause of admission. Out of 212 surgical cases, 78.7% were male. Most common surgical procedure is K wire fixation for fracture. Conclusion: Orthopedic service at Karnali Academy of Health Sciences has continuously been delivered amidst COVID 19 chaos. Orthopedics consists of major bulk of cases in our institution so proper strategy for preparation and handling of cases should be made during pandemic